Dlaczego nie mówią po polsku? - stosunek polskich uczniów do nauki języka ojczystego w Szwecji = Why don`t they speak polish? Ate attitude of Polish students to learning their mother language in Sweden - Sochacka, Anna Justyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper is a summary of the sociolinguistic survey conducted in March 2015 among adult children of Polish immigrants in Sweden. The main purpose of the study was to analyze what factors influence reluctance in learning Polish and poor performance in the adult life.
Keywords: drugie pokolenie migrantów; język polski w Szwecji; język ojczysty; polska emigracja w Szwecji; second generation of immigrants; Polish language in Sweden; Polish emigration in Sweden